2009
DOI: 10.4188/jte.55.67
|View full text |Cite
|
Sign up to set email alerts
|

Dyeing Property of Silkworm Cocoon

Abstract: Silk is usually dyed at the fabric or yarn stage. It is difficult to dye silk fibers at the cocoon stage because (1) cocoon loses its original shape and (2) dye cannot penetrate easily into the cocoon shell. This study is the first attempt at dyeing cocoons adequately while retaining their shapes. Cocoons were dyed with a reactive dye under various conditions. When the dyeing process was carried out for several hours without a surfactant, the cocoon shells were not dyed adequately from 293 K to 333 K, furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In a previous study, we reported the dyeing property of silkworm cocoon ( 4 , 5 ). Lipid oxidation on vegetable oil and frying oil using the indicators peroxide value (POV), carbonyl value (COV) and anisidin value (AnV) has been previously identified ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we reported the dyeing property of silkworm cocoon ( 4 , 5 ). Lipid oxidation on vegetable oil and frying oil using the indicators peroxide value (POV), carbonyl value (COV) and anisidin value (AnV) has been previously identified ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…This result is due to the structural differences among the shell layer portions. As described in the related paper [10], the degree of crystallinity of silk fiber at the inner portion of shell is higher than that of the outer one, so that the dye molecule easily penetrates into the outer shell, but needs more time to penetrate into the inner shell. In addition, when the dye bath was at lower pH, the penetration speed was slightly slower at over 30 minutes.…”
Section: Methodsmentioning
confidence: 96%
“…If dyeing at the cocoon stage can be controlled, silk yarn can be made with new complicated colors by reeling different-colored cocoons together, for example. In a related work [10], we have conducted silkworm cocoon dyeing using a reactive dye and have unraveled the dyeing properties depending on dyeing temperature, dyeing time and concentration of surfactant in the dye bath. In order to extend the technique of cocoon dyeing, it is important to clarify the dyeing characteristics of the cocoon using various kinds of dye.…”
Section: Introductionmentioning
confidence: 99%